Performance of Severe Acute Respiratory Syndrome Coronavirus 2 Serological Diagnostic Tests and Antibody Kinetics in Coronavirus Disease 2019 Patients - Choi, Hyun-Woo; Jeon, Chae-Hyeon; Won, Eun Jeong; Kang, Seung-Ji; Lee, Seung Yeob; Kee, Seung-Jung (Frontiers in Microbiology, 2022)
Serological testing is recommended to support the detection of undiagnosed coronavirus disease 2019 (COVID-19) cases. However, owing to the unclear kinetics of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) antibodies, the performance of serological assays has not been sufficiently evaluated. Hence, the performance and antibody kinetics of six SARS-CoV-2 binding antibody assays [three chemiluminescence (CLIAs) and three lateral flow immunoassays (LFIAs)] and a surrogate virus neutralization test (sVNT) were analyzed in a total of 988 serum samples comprising 389 COVID-19-positives and 599 COVID-19-negatives. Overall diagnostic sensitivity of CLIAs and LFIAs ranged from 54.2% to 56.6% and from 56.3% to 64.3%, respectively. Overall specificity of CLIAs and LFIAs ranged from 98.2% to 99.8% and from 97.3% to 99.0%, respectively. In symptomatic group, the positivity rate increased by over 80% in all assays at >14 days after symptom onset. In asymptomatic group, the positivity rate increased by over 80% in all assays at >21 days after initial RT-PCR detection. In LFIAs, negatively interpreted trace bands accounted for the changes in test performance. Most false-positive results were weak or trace reactions and showed negative results in additional sVNT. For six binding antibody assays, the overall agreement percentages ranged from 91.0% to 97.8%. The median inhibition activity of sVNT was significantly higher in the symptomatic group than in the asymptomatic group (50.0% vs. 29.2%; P < 0.0001). Median time to seropositivity ranged from 9.2 to 9.8 days for CLIAs, 7.7 days for LFIA IgM, 9.2 days for LFIA IgG, and 8.8 days for sVNT, respectively. There was a strong positive correlation between the quantitative results of the four binding antibody assays and sVNT with Spearman ρ values ranging from 0.746 to 0.854. Testing and interpretation of the antibody assays should be performed based on patient’s contact history, symptoms, time of illness, measured assays, antigens, and target antibodies. In particular, when using LFIAs, we recommend using more objective interpretable assays or establishing a band interpretation system for each laboratory, accompanied by observer training. We also anticipate that sVNT will play an important role in SARS-CoV-2 antibody testing and become the practical routine neutralizing antibody assay.